Variasi Jenis Humektan pada Formulasi Sediaan Masker Gel Peel Off Ekstrak Kulit Buah Pisang Kepok (Musa paradisiaca pericarpium) - Frida Ardina Pratiwi; Surya Amal; Fitria Susilowati (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2018)
Peel-off gel mask is one type of facial mask that has advantages in its use that is easily removed or released like an elastic membrane. This study aims to determine the kepok banana peelcan be formulated into a peel-off gel mask and the effect of adding properly humectant so that the product of peel-off gel mask is effective, stable, and safe in its use. The gel mask formulation is made with Polyvinyl Alcohol (PVA) base on 13% concentration. Evaluations of gel mask preparation include observation of changes in color, odor, texture, pH, dry time, dispersion and viscosity for 28 days at 40ºC storage temperature. The result data of peel-off gel mask preparation is analyzed by SPSS 16.0, with one way ANOVA. The results showed that humectant variation significantly affected organoleptic and drying time (p < 0.05) and humectant variation significantly did not affect pH, homogeneity, viscosity and dispersion (p > 0,05). The best formula of the facial mask extract from the Musa paradisiaca pericarpium peel extract in the form of peel off gel based on the organoleptic test and the dry time is the formula three, which is honey as humectant.